2010
DOI: 10.1007/s00216-010-4099-4
|View full text |Cite
|
Sign up to set email alerts
|

Total internal reflection ellipsometry as a label-free assessment method for optimization of the reactive surface of bioassay devices based on a functionalized cycloolefin polymer

Abstract: . (2010) Total internal reflection ellipsometry as a label-free assessment method for optimization of the reactive surface of bioassay devices based on a functionalized cycloolefin polymer. Analytical and Bioanalytical Chemistry, 398 (5). pp. 1927-1936. ISSN 1618-2642 Abstract:We report a label-free optical detection technique, called total internal reflection ellipsometry (TIRE), which can be applied to study the interactions between biomolecules and a functionalized polymer surface. Zeonor (ZR), a cyclo ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…Similar findings were observed by Yuan et al [45] using SPR when they tried to improve the immobilization capacity of anti-rabbit IgG and antigen binding using chitosan/alginate layer-by-layer self-assembled multilayer films. Le et al [46] also confirmed, by using total internal reflection ellipsometry, that an increase in surfaceadsorbed anti-R-hCG resulted in the reduction of hCG binding efficiency.…”
Section: Optimization Of Antigen Binding To the Immobilized Antibodiementioning
confidence: 88%
“…Similar findings were observed by Yuan et al [45] using SPR when they tried to improve the immobilization capacity of anti-rabbit IgG and antigen binding using chitosan/alginate layer-by-layer self-assembled multilayer films. Le et al [46] also confirmed, by using total internal reflection ellipsometry, that an increase in surfaceadsorbed anti-R-hCG resulted in the reduction of hCG binding efficiency.…”
Section: Optimization Of Antigen Binding To the Immobilized Antibodiementioning
confidence: 88%
“…PsiDelta 2 software (Jobin Yvon Horiba, France) was used for fitting the data from the measured Ψ and Δ spectra from TIRE to obtain the thickness of the ssDNA layers. Details of the fitting procedure were described elsewhere 18…”
Section: Methodsmentioning
confidence: 99%
“…The fabrication method of the PMMA flow-cell has been reported elsewhere [21]. For deposition of BSA and DOTAP, a standard COP slide was glue to the top PSA layer of a PMMA flow-cell to form a close channel as shown in Fig 1(b).…”
Section: Deposition Of Blocking Agents Into Pmma Microfluidic Flow-cellsmentioning
confidence: 99%
“…Fluorescent intensity was measured inside the microwells of the PMMA flow-cells to evaluate the effectiveness of each coatings against the non-specific adsorption of Cy5-labeled anti-IgG. Finally, total internal reflection ellipsometry (TIRE) [14][15][16][17][18][19][20][21] with spectra and kinetic data of adsorption of anti-a-human chorionic gonadotropin (anti-a-hCG) was used to evaluate the stability of the coatings under buffer rinsing. Our results could be useful when choosing a blocking agent, its deposition and characteristics, for suppression of non-specific binding of biomolecules on a PMMA surface.…”
Section: Introductionmentioning
confidence: 99%